Work-related training and the new National Minimum Wage in Britain - Wiji Arulampalam; Alison L. Booth; Mark L. Bryan (University of Essex, Institute for Social and Economic Research (ISER), 2003)
In this paper we use important new training and wage data from the British Household Panel Survey to estimate the impact of the national minimum wage (introduced in April 1999) on the work-related training of low-wage workers. We use two treatment groups for estimating the impact of the new minimum wage those workers who explicitly stated they were affected by the new minimum and those workers whose derived 1998 wages were below the minimum. Using difference-in-differences techniques for the period 1998 to 2000, we find no evidence that the introduction of the minimum wage reduced the training of affected workers, and some evidence that it increased it. In particular we find a significant positive effect of about 8 to 11% for affected workers. Consequently our findings can be interpreted as providing no evidence in support of the orthodox human capital model as it applies to work-related training, and some evidence in support of the new theories based on imperfectly competitive labour markets. Our estimates also suggest that two of the goals of the UK government improving wages of the low paid and developing their skills have been compatible, at least for the introductory rates of the national minimum wage.
Keywords: 330